Entrepreneurship education impact on entrepreneurial intention: theory of planned behaviour approach - Mahfud, Tuatul; Jati Kusuma, Bambang; Channa, Khieng; Dang, Vu Hung (Journal of Education and Learning (EduLearn), 2025)
The food industry plays a substantial role in the economic development of every nation. Furthermore, intention has a crucial influence on fostering the emergence of new entrepreneurs. While numerous studies have emphasised the significance of cultivating entrepreneurial intentions, there is a scarcity of research investigating the process by which culinary entrepreneurial intentions (foodpreneurial) are developed among vocational high school students. This study investigates the construction and evaluation of a framework for fostering entrepreneurial aspirations among vocational high school students specialising in culinary arts, employing the theory of planned behaviour (TPB) methodology. The participants in this sudy were vocational high school students who were asked to provide their perspectives on various aspects, including entrepreneurship education, attitudes towards the behaviour, perceived behavioural control, subjective norms, and foodpreneurial intentions. Structural equation modelling (SEM) data analysis facilitated by the SmartPLS software. This study findings indicate that vocational high school students’ intentions to engage in culinary entrepreneurship are significantly impacted by their attitudes towards the activity, their perception of behavioural control, and subjective norms. Furthermore, entrepreneurial education influences entrepreneurial intentions via the three antecedent factors of the TPB. The findings of this research carry significance for both theoretical and practical advancements concerning the process by which entrepreneurial intentions are formed among students enrolled in vocational high schools and vocational higher education.